The Impact of Foreign Direct Investment on Economic Growth in Nigeria - Ibrahim, Sani Ali (Information Management and Business Review, 2015)
The economic development performance can be used to measure the economic growth of a given country. In economic analysis, a country can attain economic growth through the growth in national income measurement. However, there were rigorous discussions on the role of foreign direct investment (FDI) on economic growth and continued to be a topic of discussion on the contemporary economy. This paper serves as an extension to the previous empirical studies on the issue by providing some evidence from time series data for the period 1971 to 2013 of Nigeria. The primary aim of this study is to analyze the impact of FDI on economic growth of Nigeria taking trade openness, Gross Fixed Capital Formation and human capital as control variables. To investigate the long run equilibrium relationship, Johansen and Juselius co-integration approach is analyzed, while the speed of adjustment in the short run is analyzed through the use of VECM method. In Nigeria, FDI, GFCF and HK have long run relationship with economic growth. However, the coefficient of ECM in Nigeria is statistically significant at 1% level of significance. Thus, 10.8% of the adjustment is achieved due to the correction of the adjustment speed in a year.